Dyslipidemia Is Related to Mortality in Critical Patients With Coronavirus Disease 2019: A Retrospective Study - Yue, Jiang; Xu, Hua; Zhou, Yong; Liu, Wen; Han, Xiaofeng; Mao, Qing; Li, Shengxian; Tam, Lai-Shan; Ma, Jing; Liu, Wei (Frontiers in Endocrinology, 2021)
Background: So many patients with critical coronavirus disease 2019 (COVID-19) suffer from multiple organ dysfunctions in intensive care unit (ICU) in Wuhan, China. However, whether the dyslipidemia is associated with the prognosis of COVID-19 is unclear. Methods: A retrospective study was performed in critical patients (N=48) with coronavirus disease 2019 to examine the parameters in serum, such as glucose, lipid profiles, liver function and kidney function, who were hospitalized in Leishenshan hospital between February and April 2020 in Wuhan. Data were collected when they were on admission, 2-3days after admission and last test before the achievement of clinical outcome. Results: There were more male patients than female patients in the critical cases. Albumin value and creatine kinase (ck) value were statistically decreased at 2-3days after admission compared with those on admission (P<0.05). Meanwhile, low density lipoprotein (LDL-c), high density lipoprotein (HDL-c), apolipoprotein A (ApoA) and apolipoprotein A (Apo B) levels also statistically decreased at last tests before achievement of clinical outcome comparing with those at admission (P<0.05). Logistic regression showed that HDL-c level both on admission and last test before achievement of clinical outcome were closely associated with mortality in critical patients with COVID-19. At the same time, logistic regression also indicated that total cholesterol (TC) level at 2-3days after admission was also related to mortality in critical patients with COVID-19. Conclusions: There were deteriorative disorders in lipid metabolism among the critical patients with COVID-19. The development of hypolipidemia may be involved in the progression of critical COVID-19.